2021
DOI: 10.1021/acsami.0c18933
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healing Coatings Containing Core–Shell Nanofibers with pH-Responsive Performance

Abstract: The micro−nanofibers prepared by the electrospinning technique can be used as a good container for loading healing agents. The core−shell electrospun nanofibers with polyacrylonitrile as the outer shell and tannic acid (TA) and tung oil as the core healing agents were synthesized by a coaxial electrospinning method and exhibited pH-sensitive ability. The nanofibers as additives were added to an epoxy resin coating as a self-healing coating. The morphological stability of the electrospun nanofibers were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…Most of the self‐healing coatings researched at present rely on local ultraviolet radiation or heating to complete the self‐healing. [ 48–51 ] Making rapid self‐healing coatings without external energy is still a challenge. Moreover, coating materials often face many complex environments, which require coating materials to have certain reliable mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the self‐healing coatings researched at present rely on local ultraviolet radiation or heating to complete the self‐healing. [ 48–51 ] Making rapid self‐healing coatings without external energy is still a challenge. Moreover, coating materials often face many complex environments, which require coating materials to have certain reliable mechanical properties.…”
Section: Resultsmentioning
confidence: 99%
“…In Figure 6, R s is the solution resistance, and R c and CPE -1 represent the coating resistance and coating capacitance, respectively. R ct and CPE -2 represent the charge-transfer resistance and double-layer capacitance, respectively (Wang et al, 2021;Cui et al, 2018). Figure 8A was used to fit the EIS data for PA/G/EP during the 96-h immersion, and Figure 8B was used to fit the EIS data which have two time constants (Pan et al, 2020).…”
Section: Corrosion Performance Of the G Modified Epoxy Surface Tolerant Coatingmentioning
confidence: 99%
“…Due to their ability to be ionized in an aqueous environment, applications using polyelectrolytes can be found across many disciplines, such as in medicine, mineral separation, paints, food industry, corrosion inhibition, water purification and filtration, or cosmetics. [10,13,[22][23][24][25][26][27] In the past decades, the design of pH-responsive biomedical systems has been the focus of many research groups as for example shown by responsive lipid or polymeric nanoparticles using ionizable polymers. [28][29][30][31][32][33] This is attributable to the wide range of pH-differences found within the human body and the numerous pathological conditions inducing pH changes occuring for example in tumors, due to inflammation or during the wound healing process.…”
Section: Introductionmentioning
confidence: 99%